Visualizing national and international deaths with data during the COVID-19 pandemic - Appelgren, Ester; Morini, Francesca; Maya, Amanda (Journalistica, 2025)
This study focuses on the difference between international and national COVID-19-related deaths in European countries. It is an exploratory study based on a content analysis with elements of both quantitative and qualitative representations of death by COVID-19 within a sample of 255 data visualizations. The visualizations were included in 97 news articles published by media outlets online, across ten European countries between February 2020 and April 2022. The nature of this study is interdisciplinary. It includes methods, theory and scientific contribution from Journalism Studies, a subfield of Media and Communication studies, and Visualization research, a subfield of Human and Computer Interaction. Results indicate that similar to how journalism traditionally covers crises such as war, journalistic visualizations about the COVID-19 pandemic included differences in representing national deaths compared to international deaths. We also found indications of death being subtly diminished or dramatized with techniques of statisticulation to distract audiences from national death counts and comfort them in times of crisis. Despite the global implications and consequences of the pandemic and journalists’ effort to report beyond national boundaries, the enforcement of national interests has been the priority.